The Effect of Toxic Leadership on Employee Silence: The Mediating Role of Workplace Bullying and Organizational Cynicism A Field Study - Abu El Dahab, Mohamed Sobhy Ahmed (The Arab Journal of Administration, 2024)
This research aimed to measure the mediating effect of workplace bullying and organizational cynicism on the relationship between toxic leadership and employee silence within the Suez Canal Authority. The research was conducted on a sample of (314) employees working in Suez Canal Authority using the survey methods. The results of path analysis showed that the partial mediation was achieved, as the value of the indirect effect of toxic leadership on employee silence through the median variable (workplace bullying) (0.475) was statistically significant, and the value of the indirect effect of toxic leadership on employee silence through the median variable (organizational cynicism) (0.50) also was statistically significant, while workplace bullying and organizational cynicism together full mediated the relationship between toxic leadership and employee silence. The research recommends that the need to increase awareness of workplace bullying and organizational cynicism dangers, and reducing the reasons for the emergence of these behaviors within the Suez Canal Authority, as well as to establish a good mechanism for selecting leaders that includes a set of rules and criteria that ensures the exclusion of individuals with hostile and toxic behaviors toward their co-Workers.